GEOGRAPHY, LABOR AND HEALTH: SENSE OF LIFE ON SPEECH OF THE PEOPLE WITH AMIOTROFIC LATERAL SCLEROSIS - Simon, Carolina Russo; Guimaraes, Raul Borges [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2016)
This article is the result of studies carried out in CETAS regarding the fight for life of people with Amyotrophic Lateral Sclerosis (ALS). From the collected reports in the research, we identified the centrality of labor in the human condition of these subjects, which led us to reflect on the promotion of health in the Geography of Health and Labor.
Keywords: ontology; labor; health promotion; ALS